Traditional Festivals in Southeast Asia: Unity in Diversity - Minh Tri Nguyen (Penerbit Jurnal Indonesia, 2025)
Traditional Southeast Asian festivals serve as vibrant expressions of cultural identity, reflecting historical continuity and regional diversity. Rooted in indigenous traditions and influenced by external cultural exchanges, these festivals embody the concept of